Palliative Care 2019
DOI: 10.5772/intechopen.84730
|View full text |Cite
|
Sign up to set email alerts
|

Communication with Families in the Last Days of a Patient’s Life and Optimal Delivery of a Death Pronouncement

Abstract: Communicating with family members is critically important when a severely ill patient is experiencing their last few days of life. However, healthcare professionals (HCPs) have limited opportunities to learn effective and respectful ways to perform this communication. In recent decades, significant effort has been put forth to identify the phenomena that indicate the last hours and days of life and the optimal methods to deliver a death pronouncement, which will potentially help HCPs communicate compassionatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…There is a paucity of literature on teaching DWLE with most focusing on DP [11]. Additionally, although many schools deliver education around end-of-life care, there is less published about delivering death news [11].…”
Section: Usefulness Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of literature on teaching DWLE with most focusing on DP [11]. Additionally, although many schools deliver education around end-of-life care, there is less published about delivering death news [11].…”
Section: Usefulness Discussionmentioning
confidence: 99%
“…There is a paucity of literature on teaching DWLE with most focusing on DP [11]. Additionally, although many schools deliver education around end-of-life care, there is less published about delivering death news [11]. Physician-patient-family communication and physician behavior during a DP is an important component of DWLE.…”
Section: Usefulness Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family communication includes daily conversations, conflict resolution, decision-making, and emotional expression that the place between family members. It has been shown that family communication relating to death will affect family members’ emotional responses and long-term mental health ( 44 ). If family communication is smooth, open, and positive, parents are more likely to establish a sense of trust and understanding with their children.…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%